(untitled) (Iraqi Journal of Science, 2023)
The present study conducted on 120 obese males and 50 healthy males, their age ranged from 20-50 years. The patients were divided into 3 groups based on Body Mass Index (BMI) and Central Obesity (CO), it has noticed that there is a significant relation between both indexes. The DNA was isolated from the blood of patients and applies for PCR by using designed primers for exons 1 and 3 of GCG gene. The results showed that there are mutants in exon 1 at locus 9573 (G/C) for 30 patients and locus 9864 (C/-) for 10 patients with X2 = 12.30, also it has fund mutants in exon 3 at locus 5397 (A/G) for 28 patients and locus 5434 (G/A) for 8 patients with X2 = 11.11. These mutants have a high significant effect P≤ 0.001 to cause pathogenicity.